Adsorption of reactive yellow BF-3R dye by CTABr modified zeolite NaY (Research, Society and Development, 2021)
Textile industries generate effluents composed of organic salts and complexes from dyes not fixed on fabrics, or not degraded by the inefficiency of conventional treatment processes, which represents a high potential for environmental impact due to inadequate disposal of the generated effluent. Zeolites are porous materials that have a three-dimensional structure containing tetrahedrals of AlO4 e SiO4 which can be modified to improve its properties. The adsorption process using zeolites as adsorbents can be considered an excellent economic physical treatment to solve or minimize such a problem. This work presents an experimental study focusing on the preparation and characterization of zeolite NaY and modified with organic surfactant cetyltrimethylammonium bromide (CTABr) intended to be used as adsorbent in the process of removing yellow dye BF-3R in dye-water system batch system. The samples were characterized by X-ray diffraction (XRD), Infrared spectroscopy (IR) and thermogravimetry (TG). The effect of process parameter such as pH was studied. Results revealed that even though the modified cetyltrimethylammonium bromide organic surfactant (CTABr) did not cause alterations on the zeolite NaY structure. The IR results revealed that CTABr was successfully incorporated to zeolite NaY structure. The best conditions were established with respect to pH to saturate the available sites located on the zeolite NaY and NaY_CTABr surface. The maximum adsorption capacities were 3.35 and mg/g for dye 5.35 using as-synthesized zeolite NaY and CTABr modified zeolite NaY. Modified zeolites are excellent adsorbents for removing reactive dyes from industrial wastewater.